Design of Star Delta Control Circuit Work System on 3 Phase Electric Motor - Patabo, Muchdar; Bijang, Hatanael; Kantohe, Dostenny; Enoch, Wellem; Najoan, Jeriko; Sibuea, Heartyara (Jurnal Impresi Indonesia, 2024)
Induction motors are one of the main components in the industrial world because they have several significant advantages. These advantages include a more economical price compared to other types of electric motors, relatively lighter weight, and simple construction that facilitates the maintenance process and reduces overall maintenance costs. The purpose of this research is to reduce the surge in electric current when the motor is started and increase energy efficiency. One method commonly applied in the use of induction motors is the star-delta configuration. This configuration is used primarily to save energy by reducing the energy consumption associated with high starting currents in induction motors. The star-delta method changes the motor winding connections from star to delta configuration when the motor reaches a certain speed, thereby reducing the starting current to one-third of what it would be under direct-on-line conditions. This greatly helps in reducing the stress on the power system, as well as increasing the operational life of the motor. The system has also proven to be compliant with industrial safety regulations. In this project, it can be concluded that the star delta circuit functions when pressing the star button, the motor will move slowly. Then when pressing the delta button, this circuit also has 3 buttons namely star, delta and off.